2013
DOI: 10.1002/pca.2449
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantitation of Furanocoumarins and Flavonoids in Grapefruit Juice using Ultra‐Performance Liquid Chromatography

Abstract: Introduction Grapefruit juice can increase or decrease the systemic exposure of myriad oral medications, leading to untoward effects or reduced efficacy. Furanocoumarins in grapefruit juice have been established as inhibitors of cytochrome P450 3A (CYP3A)-mediated metabolism and P-glycoprotein (P-gp)-mediated efflux, while flavonoids have been implicated as inhibitors of organic anion transporting polypeptide (OATP)-mediated absorptive uptake in the intestine. The potential for drug interactions with a food pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…For example, the IC 50 values of silibinin and isolated constituents silybin A and silybin B (,10 mM) were more than 10 times lower than mean colorectal tissue concentrations following oral administration of 1400 mg silibinin to cancer patients (;140 mM) (Hoh et al, 2006). Likewise, the IC 50 values of naringin and naringenin (,10 mM) were at least 30 times lower than concentrations in citrus juices (.300 mM) (Erlund et al, 2001;Vandermolen et al, 2013). Finally, the IC 50 values of kaempferol and quercetin, which are present Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the IC 50 values of silibinin and isolated constituents silybin A and silybin B (,10 mM) were more than 10 times lower than mean colorectal tissue concentrations following oral administration of 1400 mg silibinin to cancer patients (;140 mM) (Hoh et al, 2006). Likewise, the IC 50 values of naringin and naringenin (,10 mM) were at least 30 times lower than concentrations in citrus juices (.300 mM) (Erlund et al, 2001;Vandermolen et al, 2013). Finally, the IC 50 values of kaempferol and quercetin, which are present Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This method was modified from a study measuring furanocoumarins in teas, fruits and vegetables that reported MeOH to be the most efficient solvent [25]. Grapefruit juice was extracted as described previously [13] by shaking 240-mL aliquots of juice with three consecutive washes of ethyl acetate (EtOAc).…”
Section: Methodsmentioning
confidence: 99%
“…At least one supplement, SciFit DHB 300, was labeled to contain 300 mg of pure DHB in each capsule and was presumably intended to be taken concomitantly with other products of the consumer's choice. Grapefruit juice contains between 2.5 and 36.3 μM bergamottin and 0.2 and 89.0 μM DHB [11-13], equating to between 0.2 to 2.9 mg bergamottin and 0.02 to 7.4 mg DHB per 8-oz (240-mL) serving. Grapefruit juice containing 2.2 mg bergamottin and 2.7 mg DHB per 240-mL serving doubled median area under the curve of felodipine relative to control [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported to be an effective agent to treat breast cancer [8], progression of hyperglycemia [7], and cardiac diseases [9]. Naringin was determined in human plasma, rat plasma, food products, and different herbal formulations by liquid chromatography-mass spectrometry (LC-MS) [10], ultra-performance liquid chromatographytandem mass spectrometry (UPLC-MS/MS) [11], LC-MS/MS [12], and ultra high-performance liquid chromatography (UHPLC) [13]. The HPTLC fingerprint profile was reported on R. vesicarius [14], but a complete validated stability-indicating analytical method has not been reported yet for the quantification of naringin in the stems and leaves of R. vesicarius.…”
Section: Introductionmentioning
confidence: 99%